Reliability, validity, and writing assessment - Dobrić, Nikola (ELOPE (Ljubljana), 2018)
Looking at the issue of validity and test validation, the historical and the theoretical progression has been well described both when it comes to educational assessment in general and language assessment in particular. A clear progression can be seen starting in the 1920s and culminating in the late 1980s/early 1990s (with minor notable developments since), and it is an advancement motivated and driven almost solely by new theoretical and practical considerations. Securing validity and validation with regard to writing assessment in particular, however, took a more winding route and was primarily shaped by a power struggle between externally administered standardized testing (and the supporting administrative bodies) on one side, and the practicing teachers of writing at higher education institutions on the other. The paper at hand outlines this evolution and gives a timeline of the events and major developments that have fueled it and explores the cutting edge of today.
Keywords: jezikovno testiranje; ocenjevanje pisanja; pregledi; standardizacija; validacija; veljavnost; zgodovinski razvoj